The rising tide lifts all boats? Income support measures for employees and self-employed during the COVID-19 pandemic - Michael Christl; Silvia De Poli; Viginta Ivaškaitė-Tamošiūnė (Global Labor Organization (GLO), 2024)
This paper examines the extent to which fiscal policy protected household incomes in the second year of the COVID-19 pandemic in EU countries. Using microsimulation techniques and detailed Eurostat data, we analyse this impact separately for employees and the selfemployed. We show that while on average income protection was similar for employees and the self-employed at the EU level, the heterogeneity both between and within countries was much higher for self-employed households in 2021. For employees, both monetary compensation schemes and unemployment benefits played a similar role in absorbing the income shock, whereas for the self-employed it was mainly monetary compensation schemes and much less so unemployment benefits that stabilised their income. Overall, we find that monetary compensation schemes, together with automatic stabilisers, absorbed a substantial part (67%) of the market income shock in 2021, albeit with a reduced cushioning effect compared to the previous year (74%). Monetary compensation schemes alone account for almost a third of this cushioning effect in 2021. Our paper underlines the importance of targeted policies to ensure comprehensive support for vulnerable households amid ongoing economic uncertainties.
Keywords: D31; E24; H24; 330; COVID-19; Self-employed; Income stabilisation; Microsimulation; EUROMOD